The Hitchcock Romance : Love and Irony in Hitchcock's Films. - Brill, Lesley (Book collections on Project MUSE., 1988)
Was Alfred Hitchcock a cynical trifler with his audience's emotions, as he liked to pretend? Or was he a profoundly humane artist? Most commentators leave Hitchcock's self-assessment unquestioned, but this book shows that his movies convey an affectionate, hopeful understanding of human nature and the redemptive possibilities of love. Lesley Brill discusses Hitchcock's work as a whole and examines in detail twenty-two films, from perennial favorites like North by Northwest to neglected masterpieces like Rich and Strange.